Photoelectrochemical Performance of G-C3N4 for Hydrogen Production - Thurga Devi, Munusamy; Chin, Sim Yee; Khan, Md. Maksudur Rahman (Penerbit UMP, 2022)
Global energy crisis keeps arising and converting intermittent energies into storable chemical fuels, especially hydrogen is indeed a crucial obligation. Water splitting through photoelectrochemical (PEC) is certainly a promising technology intended for the current dilemma. Nevertheless, the broad applications of this system mainly depends on the exploration of efficient electrode materials. Accordingly, graphitic carbon nitride (g-C3N4) has high potentiality as a photoelectrode material for PEC water splitting. In the present work, g-C3N4 was fabricated by thermal polycondensation technique and characterised by numerous analysis techniques, including XRD, FTIR, UV-Vis and Mott-Schottky. The hydrogen evolution was deliberated by electrochemical analysis in the three-electrode PEC system. LSV analysis revealed that during the light irradiation, the current generated was higher (0.45 mA/cm2), whereby the current density represents the amount of hydrogen gas evolved.